Superior-segment Bilateral Facet Violation in Lumbar Transpedicular Fixation, Part I: A Biomechanical Study of Blocking Superior Facets. Issue 11 (1st June 2020) - Xu, Yunfeng; Le, Xiaofeng; Zhang, Qi; Kuai, Shengzheng; Leng, Huijie; Duan, Fangfang; Shi, Zhan; Liu, Bo; He, Da; Lang, Zhao; Wu, Jingye; Wang, Ling; et al.
Abstract : Study Design: This is an in vitro biomechanical study. Objectives: The aim of this study was to investigate the biomechanical variations of lumbar spine motor units and that under different moments after screw heads blocking superior-adjacent bilateral facets through the cadaver specimen biomechanical experiment. Summary of Background Data: Facet joint violation by pedicle screws is not a rare adverse event in instrumented lumbar fusion surgery, and one of the most common types is the screw head blocking the superior-adjacent facet. However, its contribution to biomechanical instability at the supradjacent level is unknown. Methods: The range of motion (ROM) of 12 lumbar spines (L4-S1) were measured in flexion-extension, lateral bending, and axial rotation for L4/5. All specimens were randomly divided into two groups: the control group and the blocking group, each with 6 specimens. Spine were tested on intact and instrumented specimens, respectively. The relative ROM changes were compared between the blocking and control groups. Results: In the blocking group, the supradjacent-level flexion-extension ROM significantly decreased under all moments (7.5, 6.0, 4.5 Nm) relative to the intact spine and a significant decrease in the lateral bending relative ROM was found at 4.5 Nm. In the control group, no significant change of supradjacent-level ROM was found relative to the intact noninstrumented spine at each moment. When performing flexion-extension, the relative ROM change between the 2 groups was significantly different at 4.5 Nm. When performing lateral bending, the relative ROM change between the 2 groups was significantly different at moments of 6.0 and 4.5 Nm. Conclusion: When screw heads blocked superior-adjacent bilateral facets, the supradjacent-level flexion-extension ROM and lateral bending ROM decreased. In the long run, this may be a risk of persistent low-back pain due to frequent impingement. Level of Evidence: N/A Abstract : In the blocking group, the supradjacent-level flexion-extension range of motion (ROM) decreased significantly under all moments relative to the intact noninstrumented spine, and the lateral bending ROM decreased at 4.5 Nm. In the control group, the supradjacent-level ROM did not change significantly relative to the intact noninstrumented spine at each moment.